Pengaruh Marinasi Belimbing Wuluh (Averrhoa bilimbi) terhadap Waktu dan Suhu Penyimpanan Daging Ayam Broiler dan Ayam Kampung di Pasar Bantengan - Farsya Auliya Zulfany; Narto; Choirul Amri; Sri Haryanti (MEJORA Medical Journal Awatara, 2025)
Averrhoa bilimbi (bilimbi) contains 10% saponins, 6% tannins, as well as alkaloids, phenols, and flavonoids, which are suspected to have antibacterial properties and can be used as natural food preservatives. To determine the effect of 12% bilimbi marination on the reduction of bacterial counts in broiler and native chicken meat based on variations in storage temperature and duration. This study used a quasi-experimental design with a one-group pretest-posttest method. Samples of broiler and native chicken meat were marinated with 12% bilimbi solution and stored at room and cold temperatures for 24 and 36 hours. Microbiological testing was conducted using the Total Plate Count (TPC) method, and data were analyzed using the Paired Sample T-test. The highest average reduction in bacterial count was observed in broiler chicken stored at room temperature for 36 hours (68.09%), while the lowest was found in native chicken stored at cold temperature for 24 hours (18.59%). Statistical analysis showed that 6 out of 8 treatments had significant differences before and after marination (p<0.05), while 2 treatments showed no significant difference (p>0.05). Marination with 12% bilimbi extract is effective in reducing bacterial counts in chicken meat, particularly during room temperature storage for up to 36 hours.